1987
DOI: 10.1515/znb-1987-0320
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between the Molecular and Crystal Structures of a Benzylpenicillin Ester and its Corresponding Sulfoxide with Drastically Reduced Biological Activity

Abstract: A comparative X-ray structure determination was performed to elucidate possible conformational differences between penicillins and penicillin sulfoxides. Penicillin-G-acetoxy-methylester and its β-oxide were used as model substances, because the only chemical difference between both compounds resides in the thiazolidine ring sulfur oxidation. On the basis of the X-ray data as well as of infrared measurements it is discussed that the drastically reduced biological activity of the penicillin-G-sulfoxide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 8 publications
1
4
0
Order By: Relevance
“…The geometrical structural parameters found in the study by Labischinski et al11 can be confirmed by the low‐temperature measurements. ORTEP22 plots including the chosen atomic‐numbering scheme are shown in Figure 1.…”
Section: Resultssupporting
confidence: 67%
See 2 more Smart Citations
“…The geometrical structural parameters found in the study by Labischinski et al11 can be confirmed by the low‐temperature measurements. ORTEP22 plots including the chosen atomic‐numbering scheme are shown in Figure 1.…”
Section: Resultssupporting
confidence: 67%
“…As a consequence, the ester group is axial in 1 and equatorial in 2 . Further discussions on structural parameters can be found in the Labischinski paper 11…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, the amide bond geometry of structurally characterized β-lactams presented in Figures and can be characterized as N-pyramidalized (average χ N of 54.4°), while twist is less significant (average τ of 19.2°), as expected from the geometry of the fused four-membered ring system. There is only a very scattered correlation between N-pyramidalization and twist of the amide bond, with the general trend of higher twist with increased nitrogen pyramidalization ( R 2 = 0.30).…”
Section: Cyclic Amides: N-pyramidalization 40–60°mentioning
confidence: 86%
“…The most common are [ 2 .4.0] and [ 2 .3.0] ring systems with the six-membered ring such as 1,3-oxazinane (e.g., 4.30 ), and more common five-membered ring, such as thiazolidine 1,1-dioxide (e.g., 4.32 ), thiazolidine 1-oxide (e.g., 4.33 ), thiazolidine (e.g., 4.34 ), 1,3-selenazolidine (e.g., 4.36 ), pyrrolidine (e.g., 4.81 ), imidazolidine (e.g., 4.94 ), or oxazolidine (e.g., 4.101 ) . In general, more dense substitution of the fused ring, in particular at the α-positions to the nitrogen atom and the carbonyl group and ring unsaturation, result in higher N-pyramidalization. These N-pyramidalized amides are well-known to be highly reactive as acylating reagents and are important pharmacophores in medicinal chemistry research.…”
Section: Cyclic Amides: N-pyramidalization 40–60°mentioning
confidence: 99%